Increasing fruit and vegetable consumption in grade-school children - Ryan, Linda DeBell, author; Anderson, Jennifer, advisor; Bechtel, Peter J., advisor; Kendall, Patricia, committee member; Keefe, Thomas, committee member; Jansen, Duane, committee member (Colorado State University. Libraries, 1997)
Diets rich in fruits and vegetables have many health benefits. Nutrients in fruits and vegetables such as vitamins, minerals, and fiber help protect individuals from certain cancers and cardiovascular disease. Children in our nation are not meeting the national health objectives or recommendations to eat plenty of fruits and vegetables. This research assessed whether the provision of classroom nutrition education on the benefits of eating fruits and vegetables and providing more fresh fruits and fresh vegetables in the school lunch program increased consumption by grade-school children. This research was completed in three parts. The purpose of part one (The Nutrition Education Intervention Study) was to determine if providing nutrition education to grade-school children and the community increased fruit and vegetable consumption. In this study a nutrition education program was given to the grade-school children and community of Holyoke (experimental group). The effects of the nutrition education intervention were compared to the control group (i.e., the grade-school children and community of Haxtun), which received no intervention. A nutrition education program was developed and designed as a hands-on education program for the children and for the community. The intervention included nutrition education materials, demonstrations, and activities on increasing the consumption of fruits and vegetables and good nutrition. Fruit and vegetable consumption was measured by a 24-hour food recall (children only) and a pre- and post-questionnaire for the children and community. The results showed mean fruit and vegetable consumption increased by 1.37 servings per day (from 2.45 to 3.82) among the grade-school children using the 24-hour food recall assessment method and 0.93 (3.93 to 4.86) using a pre/post self-reported questionnaire (both at p[less than or equal to]0.05 ). The community's mean fruit and vegetable intake increased by 0.66 servings per day (3.28 to 3.94) from the pre to post questionnaire (p[less than or equal to]0.05 ). The purpose of part two (The Fresh Fruit and Vegetable Intervention Study) was to determine if providing quality fresh fruits and fresh vegetables increased consumption by grade-school children. In this study the Department of Defense (DOD) provided fresh fruits and vegetables to schools within Colorado. The schools receiving the fresh fruits and vegetables (experimental group) were compared to schools not receiving fresh produce (control group). The children in the experimental group were offered a variety of high quality of fresh fruits and vegetables in the school cafeteria with their school lunches. Fruit and vegetable consumption was measured by subtracting plate waste from the beginning weight for each fruit and vegetable served. The results were as follows: 1. The experimental group took on an average 2. 70 ounces combined fruits and vegetables per child, the control group took 3.14 ounces per child (p[greater than or equal to]0.05). 2. The children in the experimental group consumed a greater percentage (73%) of fruits and vegetables than the control group (61 %) (p[less than or equal to]0.05). 3. The children in both groups consumed more fruits than vegetables. In part three, the results of the two studies were completed. The results showed that there was no difference in the two approaches, both interventions increased consumption of fruits and vegetables in the grade-school children.
Keywords: Children -- Nutrition; Diet therapy for children; Food consumption; Children